Prospective mathematics teachers' situational interest for word problems - Martinussen, Liva J.; Riege, Anine; Richter, Jasmin; Briseid, Eyvind Martol; Maugesten, Marianne; Reber, Rolf (Educational psychology (Dorchester-on-Thames), 2025)
This study examined the influence of word problems and individual differences on student teachers' situational interest. There is extensive research on word problems, but few studies have assessed the impact on situational interest, particularly for self-generated word problems. Using a within-subject design (N = 256), we investigated whether self-generated or ready-made word problems elicited greater situational interest compared to solving math tasks without a context (math-tasks-only). Additionally, we investigated whether individual interest in mathematics, mathematical self-concept, and related measures were associated with situational interest. Findings indicated that both word problem conditions significantly increased situational interest compared to math-tasks-only, regardless of individual interest. Self-concept moderated the effect of condition on situational interest; the self-generated word problem was more interesting for participants with higher self-concept, whereas the ready-made word problem was more interesting for participants with lower self-concept. We discuss these results considering interest-development and self-determination theory.